Cerebral Cortical Activity During Academic Stress Amongst Undergraduate Medical Students at Kampala International University (Uganda) - Mujinya, Regan; Kalange, Muhamudu; Ochieng, Juma John; Ninsiima, Herbert Izo; Eze, Ejike Daniel; Afodun, Adam Moyosore; Nabirumbi, Ritah; Sulaiman, Sheu Oluwadare; Kairania, Emmanuel; Echoru, Isaac; Okpanachi, Alfred Omachonu; Matama, Kevin; et al. (Frontiers in Psychiatry, 2022)
Background: Stress amongst medical students is related to their academic lifespan; however, information from developing countries on brain health amongst medical students continues to be scarce. The objective of the study was to establish perceived academic stress levels and assess the ability to cope with stress and investigate its effects on the visual reaction time (VRT), audio reaction time (ART), and tactile reaction time (TRT) in the somatosensory cortex amongst medical students of Uganda. Methods: This was a cross-sectional study conducted amongst preclinical (n = 88) and clinical (n =96) undergraduate medical students at Kampala International University Western Campus. A standard perceived stress scale (PSS) was used to categorize stress into low, moderate, and severe while the ability to cope with stress was categorized into below average, average, above average and superior stresscoper. Data on reaction time was acquired through VRT, ART, and TRT using the catch-a-ruler experiment and this was analyzed using SPSS Version 20. Results: The study showed that preclinical are more stressed than clinical students (PSS prevalence for low stress = preclinical; clinical: 40%, 60%). Moderate stress of 48.4% and 51.6% while high perceived stress was 75% and 25% amongst preclinical and clinical students. Amongst males and females in preclinical years, higher TRT and VRT were found than in clinical students showing that stress affects the tactile and visual cortical areas in the brain, although the VRT scores were only significantly (P =0.0123) poor in males than females in biomedical sciences. Also, highly stressed individuals had higher TRT and ART and low VRT. Superior stresscopers had high VRT and ART in preclinical and low TRT, demonstrating the importance of the visual cortex in stress plasticity. Multiple regression showed a close relationship between PSS, ability to cope with stress, age, and education level (P <0.05) demonstrating the importance of social and psychological support, especially in the biomedical sciences. Conclusion: Preclinical students suffer more from stress and are poorer stresscopers than clinical students. This strongly impairs their cortical regions in the brain thus affecting their academic productivity.